2000
DOI: 10.1177/00034894001090s503
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Bone Studies of the Human Peripheral Vestibular System

Abstract: Scarpa's ganglion cell counts were performed in 106 serially sectioned, normal human temporal bones from 75 individuals. Of these 106 bones, 15 were from neonates less than 30 days old, 14 were from infants between the ages of 1 and 12 months, and the remainder were distributed throughout each decade of life, with sample sizes ranging from 4 to 10 per decade. All temporal bones had to meet 2 criteria: no symptoms or signs of inner ear disease except for presbycusis in the medical case history and no abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 10 publications
2
58
0
Order By: Relevance
“…The technique used for SGC counts was that originally described by Schuknecht (Otte et al 1978) and used subsequently by others for the spiral and Scarpa's ganglia in human temporal bones (Velazquez-Villasenor et al 2000). All SGCs with nucleus and nucleolus were counted in each cochlear turn from every tenth section.…”
Section: Methodsmentioning
confidence: 99%
“…The technique used for SGC counts was that originally described by Schuknecht (Otte et al 1978) and used subsequently by others for the spiral and Scarpa's ganglia in human temporal bones (Velazquez-Villasenor et al 2000). All SGCs with nucleus and nucleolus were counted in each cochlear turn from every tenth section.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have demonstrated a decrease in VEMP amplitude with increasing age [Ochi and Ohashi, 2003;Su et al, 2004;Welgampola and Colebatch, 2001;Zapala and Brey, 2004]. The decrease in VEMP is not surprising considering that increasing age is related to loss of vestibular hair cells Rosenhall, 1973], vestibular nerve fibers [Bergstrom, 1973], vestibular ganglion cells [Richter, 1980;Velazquez-Villasenor et al, 2000] and vestibular brainstem neurons [Lopez et al, 1997;Tang et al, 2001]. Nevertheless, several previous studies have failed to reveal a large age-related decrease in vestibular function tests.…”
Section: Age -Amplitudementioning
confidence: 96%
“…Hair cells themselves can also undergo morphological changes with age, such as cilia disarrangement, increased cilia fragility, and development of giant cilia [95,96]. The neuronal structures relaying vestibular signals can be affected with time as well, as revealed by a decrease in Scarpa's ganglion cell number [97] and a decline in the number of primary neurons of the human vestibular system [98] in both aged humans and rats [99][100][101]. A prospective trial conducted with 70 healthy individuals traced a time-course of vestibular information integration and led to the conclusion that vestibular information reached a peak at the age of 40-49 years old and then decreased.…”
Section: Does Vestibular Aging Contribute To Osteoporosis?mentioning
confidence: 99%